Embodied collaborative writing in graduate dance education - Markula, Pirkko; Frantsi, Janita (Frontiers in Sports and Active Living, 2024)
This article explores how embodied writing can inform teaching, learning, and research presentation in graduate level dance education in a kinesiology Faculty. The focus is on a graduate dance course, ‘The Dancing Body in Motion,’ that combined the anatomical analysis of the physical body, social theory, and the lived dance experiences for more embodied and holistic teaching and learning. The authors, an instructor and a student of the course, share their experiences and reflections on the course through an embodied presentation of a dialogue that combines the instructor’s lecture notes, the student’s learning journal entries, and their reflections both separately and in conversation with each other. The reflections share insights into how embodied writing practices, such as a learning journal and performance ethnography, can bring the body and mind, material and social body, and practice and theory, together in a dance performance. This article expands the ways in which embodied writing can be used to enhance teaching and learning in graduate dance education in a kinesiology Faculty as well as a research representation.